PENGEMBANGAN MODUL INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SEKOLAH DASAR BAWAMAI PONTIANAK - Utin Nurlina; Ahadi Sulissusiawan; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was conducted based on the interest on the decreasing of the quality of education. One of them is Bahasa Indonesia learning process, especially on the speaking skill of V grade students of Bawamai elementary school Pontianak. Designing an interactive module in improving the students’ speaking skill became the focus in this research to improve the students’ speaking skill. The purpose of this research was to analyze the planning, implementation, and evaluation. Moreover, the interactive module that was used to develop the students’ speaking skill  can be used in implementation of Bahasa Indonesia learning process.This research used research and development method or qualitative approach. The object in this research was the interactive module on learning Bahasa Indonesia that is to know the result of using a module in learning process.The finding showed that designing an interactive module in improving the students’ speaking skill can be stated good and based on the criteria of designing a module. The results from three experts’ validation are 4 for the media, 4.6 for the design, and 4.62 for language materials. Meanwhile, the result of the analysis on the use of module with the average score 90.97. Based on the results, the research on designing an interactive module in improving students’ speaking skill is important to be continued because this research can be used as a source for students to improve their speaking skill.  Keywords : Designing modules, young learners, speaking skill